Increasing the role of local initiatives in creating liveable cities: Bodrum local habitat - Ozlem Dundar (European Regional Science Association (ERSA), 1998)
'Liveability' which describes the characteristics of a 'good community', was proposed by the Turkish delegation during the preparation works of Habitat II Conference, as complementary to the principle of sustainability. 'Liveable cities' were then explained in detail in Turkish National Report with stating that local liveability criteria can be developed in the hands of local initiatives. So increasing the role of local initiatives in order to make the citizens to stand as protectors to their cities, was accepted as one of the basic principles of making our cities to survive as liveable places. And the best way of achieving this goal was the formation of large city-wide meetings which collect all the actors to discuss their problems. These formations are called Local Habitats. The paper covers a discussion about the first Local Habitat realized in Bodrum on September 1996. This was the first experience in Turkey which prepared the necessary grounds of increasing the role of local initiatives in the formulation of urban policy concerns such as the physical problems originating from Bodrum's growth as one of the most important tourism centers of Turkey and the citizens' worries about its deteriorating local characteristics. This discussion will be centered around two points: The current unliveable structure of Bodrum which led to the formation of firts Local Habitat in that city and Bodrum Local Habitat's success in enabling a lot of people from the mayor to the academicians and citizens, to come together to discuss these problems in an unhierarchical organization.g
Keywords: 330